The comparison of knowledge level, perception and practice on self-medication between pharmacy staffs and visitors in Hospital Sultan Abdul Halim - Ahmad Najmi, Adriana Syuhada; Roslan, Dayana Zulaikha; Shahrulamini, Mohamad Iqmal (2018)
Self-medication is called obtaining and consuming drugs without the advice of physician either for diagnosis, prescription or surveillance (Mohamed Azhar el al., 2013). Factors influencing frequency of self-medication may be age, gender, educational level, ethnicity or beliefs. Self-medication can be good or bad for people depending on how they do it. Especially in Malaysia, the extent of self-medication is still unknown or unfamiliar to most people. Whereas, the implications of self-medication practices are increasingly recognized around the world. A research study on self-medication has been conducted. This study focuses on the comparison of knowledge level, perception and practice on self-medication between pharmacy staffs and visitors. This evaluation was done in Hospital Sultan Abdul Halim. Our targeted groups were pharmacy staffs at any age and visitors who are at the age of 18 and above. Questionnaires have been distributed to pharmacy staffs and visitors to determine their demographic profile, knowledge, perception and practices on self-medication. A knowledge score will then be calculated to determine their level of knowledge on self-medication. Convenience sampling method was used in this study. There are a total of I 00 respondents that took part in this survey, 50 were pharmacy staffs and the other 50 were visitors. The criteria for those who joined are visitors who can understand English and Bahasa Melayu and pharmacy staffs who were willing to take part in the survey. The data that we collected were analyzed using SPSS Version 20. The statistics have shown that the knowledge score of pharmacy staffs is higher (M=6.64) compared to visitors' knowledge score (M=4.72). The perception score of pharmacy staffs is also higher (M=4.74) compared to visitors' perception score (M=3. l 2). 59.57% of 94 respondents stated that their reason for practicing self-medication is minor illness whereas 11.7% used self-medication due to economic problems, 23.4% used self-medication due to time saving. and 5.32% wants quick recovery. This study reveals that the prevalence of self-medication practice among pharmacy staffs is much higher compared to visitors. The public still lacks understanding regarding self-medication. Therefore, further education regarding self-medication should be taken into consideration.